Effects of a Self-Made Workbook in College Algebra on the Students’ Academic Performance - Ubat, Joel (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to determine the effects of a self-made workbook in College Algebra on students' academic performance. The findings showed that the experimental group, which used the workbook, scored higher than the control group in all evaluations. Both groups were at the "proficiency" level, but the experimental group exceeded the control group in all 12 evaluations, with an average difference of 3.62% in favor of the experimental group. Additionally, 82.22% of students in the experimental group reached the "Advanced" level (90% and above in final grading performance), compared to only 20% in the control group (85% to 89%). The data revealed a "very high" relationship between the experimental group's performance in the 12 evaluations and their final grading performance, significant at the 5% level. This indicates that the student's performance in the evaluations strongly predicts their final grading performance. The mean performance of the experimental group in the evaluations was 3.62% higher than that of the control group, and the t-test indicated a significant difference between the two groups' performances. Similarly, the final grade of the experimental group's mean performance was 4.05% higher than that of the control group, with a significant difference confirmed by the t-test. This study implies that using a self-made workbook in College Algebra can significantly enhance students' academic performance, suggesting that tailored educational materials can improve learning outcomes. Implementing such resources could lead to higher proficiency and advanced student performance levels.